2020
DOI: 10.1021/jacs.0c08732
|View full text |Cite
|
Sign up to set email alerts
|

Streamlined Catalytic Enantioselective Synthesis of α-Substituted β,γ-Unsaturated Ketones and Either of the Corresponding Tertiary Homoallylic Alcohol Diastereomers

Abstract: A widely applicable, practical, and scalable strategy for efficient and enantioselective synthesis of β,γ-unsaturated ketones that contain an α-stereogenic center is disclosed. Accordingly, aryl, heteroaryl, alkynyl, alkenyl, allyl, or alkyl ketones that contain an α-stereogenic carbon with an alkyl, an aryl, a benzyloxy, or a siloxy moiety can be generated from readily available starting materials and by the use of commercially available chiral ligands in 52−96% yield and 93:7 to >99:1 enantiomeric ratio. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Most recently, elegant studies by Hoveyda disclosed a method for the synthesis of α‐quaternary ketones by addition into nitriles. Reactions proceed via ketimine intermediates that are hydrolyzed in situ to the corresponding ketones (Scheme 1A) [18] . Of note, the method is not limited to aryl‐substituted quaternary carbons; three dialkyl α‐quaternary ketones formed in high enantioselectivity are reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, elegant studies by Hoveyda disclosed a method for the synthesis of α‐quaternary ketones by addition into nitriles. Reactions proceed via ketimine intermediates that are hydrolyzed in situ to the corresponding ketones (Scheme 1A) [18] . Of note, the method is not limited to aryl‐substituted quaternary carbons; three dialkyl α‐quaternary ketones formed in high enantioselectivity are reported.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions proceed via ketimine intermediates that are hydrolyzed in situ to the corresponding ketones (Scheme 1A). [18] Of note, the method is not limited to aryl-substituted quaternary carbons; three dialkyl α-quaternary ketones formed in high enantioselectivity are reported. Overall, these methods are efficient and afford ketone products in excellent stereoselectivity, however, the in situ nature of the reactions renders synthesis of various dialkyl-substituted (or diaryl) quaternary stereo-centers problematic.…”
mentioning
confidence: 99%
“…Organonitriles are robust, yet versatile, compounds . We reasoned that an E - or a Z -alkenyl nitrile may be obtained through CM with purchasable fumaronitrile ( E ) or easily accessible maleonitrile ( Z ) or a mixture thereof ( 45 ) .…”
Section: αβ-Unsaturated Nitriles Esters and Acid Fluoridesmentioning
confidence: 99%
“…Hoveyda and co-workers found that using a chiral copper catalyst, the three-component coupling of allene, diboron, and nitrile furnished -substituted ,-unsaturated ketones in high regioselectivity and enantioselectivity after hydrolysis (Scheme 15). 22 Acyclic quaternary carbon stereocenters were constructed from 1,1-disubstituted allenes. Although a strong internal coordination of C=N to boron was observed in the NH-ketimine intermediate, the  stereocenter was not epimerized under the mild conditions.…”
Section: Scheme 14 Cu-catalyzed Boroacylation Of Allenesmentioning
confidence: 99%